1979
DOI: 10.1111/j.0954-6820.1979.tb06050.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Thrombolysis and Preservation of Valvular Venous Function in High Deep Vein Thrombosis

Abstract: ABSTRACT. The results of streptokinase and heparin treatment are compared in a 4‐year prospective study with special reference to preservation of high valvular venous function. An objective assessment was based upon phlebographic examinations before, during and 1–2 months after therapy. Complete lysis was demonstrated in 44% of high thromboses treated with streptokinase and in 6% treated with heparin. Retrograde phlebography revealed normal function of the proximal femoral valves in 92% of streptokinase‐treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Many trials of systemic thrombolysis for the treatment of DVT assessed early lysis, often reported bleeding, but rarely reported recurrent VTE or development of PTS (Table S13 and S14). [119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] A meta-analysis 138 summarized the fi ndings of trials that assessed mortality, recurrent VTE, major The basis for the assumed risk (eg, the median control group risk across studies) is provided in footnotes. The corresponding risk (and its 95% CI) is based on the assumed risk in the comparison group and the relative effect of the intervention (and its 95% CI).…”
Section: Systemic Thrombolytic Therapy For Acute Dvtmentioning
confidence: 99%
“…Many trials of systemic thrombolysis for the treatment of DVT assessed early lysis, often reported bleeding, but rarely reported recurrent VTE or development of PTS (Table S13 and S14). [119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] A meta-analysis 138 summarized the fi ndings of trials that assessed mortality, recurrent VTE, major The basis for the assumed risk (eg, the median control group risk across studies) is provided in footnotes. The corresponding risk (and its 95% CI) is based on the assumed risk in the comparison group and the relative effect of the intervention (and its 95% CI).…”
Section: Systemic Thrombolytic Therapy For Acute Dvtmentioning
confidence: 99%
“…W hile greatly reducing the risk of pulmonary embolism, treatment of deep vein thrombosis (DVT) with anticoagulation does not reliably preserve venous function of the lower extremity and results in a high rate (approximately 25%-30%) of recurrent venous thromboembolism and postthrombotic syndromes (1)(2)(3)(4)(5)(6). Results of many small studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) suggest that thrombolytic therapy can reduce the frequency of postthrombotic syndromes. However, because of the increased risk of bleeding, thrombolytic therapy is currently recommended for only the most severe cases of DVT (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many effective thrombolytic agents (7)(8)(9)(10)(36)(37)(38)(39), alteplase has two characteristics that make it preferable for intraclot treatment of DVT-its binding affinity for fibrin and its short half-life (approximately 5 minutes) in the general circulation. Because it binds to the fibrin in a thrombus, alteplase, unlike streptokinase and urokinase, does not need to be administered by continuous intraclot infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid thrombolysis and preservation of valvular venous function in high deep vein thrombosis may prevent post-thrombotic sequelae [32]. The occurrence of severe post thrombotic syndrome after primary treatment with isolated-pharmaco-mechanical thrombolysis device is low [33].…”
Section: Management Of Recurrent Vtementioning
confidence: 99%